Effects of different drug treatments on the proliferation of human ovarian carcinoma cell line MDAH-2774 - Ayla, Şule; Bilir, Ayhan; Ertürkoğlu, Şenol; Tanrıverdi, Gamze; Soner, Burak Cem; Sofuoğlu, Kenan; Ghisolfi, Laura; Öktem, Gülperi (Tubitak Scientific & Technical Research Council Turkey, 2018)
Background/aim: In this study, the effects of resveratrol as a natural polyphenol compound, gemcitabine as an antimetabolite that has nucleoside structure analogous to deoxycytidine, and para-aminophenol-derived paracetamol were investigated with single and combined applications in monolayers of the MDAH-2774 human ovarian cancer cell line. Materials and methods: Drugs were evaluated in cell culture with respect to cell proliferation, cell cytotoxicity (trypan blue dye exclusion test), synthesis phase of cell cycle, and cell structure in 24, 48, 72, and 96 h. Result: Resveratrol and gemcitabine diminished both cell proliferation and cell cycle synthesis phase indication in monolayer cell cultures (P < 0.05). All combination groups showed similar effects that were mainly more effective in respect to single usage of resveratrol and gemcitabine in monolayer cell cultures. Conclusion: The effects of gemcitabine, resveratrol, and paracetamol were investigated in monolayers of the MDAH-2774 human ovarian cancer cell line and a decrease in cell number in cell cycle synthesis phase, prevention of cell proliferation, and destruction of cell structure were observed.
WOS: 000431261100036
PubMed ID: 29714468
Keywords: Ovarian Cancer; Gemcitabine; Paracetamol; Resveratrol